Erenumab patient characteristics, medication adherence, and treatment patterns in the United States. Issue 4 (16th February 2021) - Hines, Dionne M.; Shah, Shweta; Multani, Jasjit K.; Wade, Rolin L.; Buse, Dawn C.; Bensink, Mark
Abstract: Objective: To describe patient characteristics, adherence, and treatment patterns, among adult migraine patients in the United States prescribed erenumab. Background: Migraine is a highly prevalent and debilitating disease characterized by recurrent attacks of moderate to severe headache accompanied by non‐headache symptoms. Erenumab is a first‐in‐class calcitonin gene‐related peptide receptor (CGRP‐R) antagonist indicated for migraine prophylaxis in adults. Methods: This retrospective longitudinal cohort study used IQVIA's open‐source longitudinal pharmacy (LRx) and medical (Dx) claims databases to identify adult migraine patients with an initial claim (index date) for erenumab between May 1, 2018 and April 30, 2019. Patients were required to have ≥180 days of follow‐up. Erenumab dosing patterns, persistence, and adherence (using medication possession ratio [MPR] and proportion of days covered [PDC]), and discontinuation of other commonly prescribed acute and prophylactic anti‐migraine therapies were assessed. Dose changes in acute therapies after initiation of erenumab were assessed in a subset of patients with an adequate trial of erenumab (≥2 additional erenumab claims within the 80 days following the index claim). Results: A total of 64, 174 patients met the study criteria. Mean (SD) age was 48 (13) years and 85.2% ( n = 54, 656) were female. The initial erenumab dose was 70 mg for the majority of patients (65.1%; n = 41, 790); most (81.4%; n = 34, 019) maintained their index dose during follow‐up. Overall, 30.8% ( n = 19, 797) of patients had a PDC ≥ 0.80 and 41.7% ( n = 26, 769) had a MPR ≥ 0.80. Discontinuation rates of acute and other prophylactic migraine therapies after initiation of erenumab (among users of the respective therapies) were 48.7% (22, 965/47, 190) and 36.1% (16, 602/46, 006), respectively. Dose decreases among triptan, ergot compound, opioid, and barbiturate users were observed after initiation of erenumab. Conclusions: Almost all patients had prior use of acute or preventive therapy. Adherence to erenumab was higher than traditional oral prophylactic migraine therapies; however, overall adherence was still suboptimal. The decrease in use of acute and preventive prescription medications following initiation of erenumab suggests effectiveness in the real‐world setting.